A prospective clinical study of foetomaternal outcome in relation to amniotic fluid index in pregnant females beyond 36 weeks of gestation at tertiary centre - Gupta, Nimisha; Nagar, Oby; Tulani, Kritika; Swami, Shraddha Kiran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Amniotic fluid plays a vital role during foetal life. The main purpose of this study was to evaluate the foetomaternal outcome in relation to amniotic fluid index in pregnant females beyond 36 weeks of gestation. Methods: This prospective type of study was conducted for one-year duration from May 2018 to May 2019 in 350 pregnant females beyond 36 weeks of gestation with clinically significant abnormal liquor volume. Clinical diagnosis was later on confirmed with ultrasonography and patients were categorized in three categories as patients with Amniotic fluid index (AFI) 5 to 24, AFI <5 and AFI > or = 25. Complete labour record was made and fetomaternal outcome was assessed. Results: In this study, incidence of oligohydramnios was found to be more than polyhydramnios at term. No significant differences were found in relation to age, parity, religion, residence and booking status in all the study groups. Mostly patients 119 (52%) delivered by caesarean section in oligohydramnios group whereas vaginal delivery was commonly seen in patients with normal AFI (80%) and polyhydramnios (55%). Growth restriction 59 (26%) and malpresentation 18 (8%) were commonly seen with oligohydramnios. In the polyhydramnios group, 14 (35%) babies had malformations whereas only 6 (3%) babies had malformations in patients with oligohydramnios. Significant differences were found in the foetal outcome between the patients with oligohydramnios and polyhydramnios in comparison to patients with normal AFI. Conclusions: In pregnant females with abnormal liquor volume increases the chances of maternal morbidity and perinatal morbidity and mortality.